2019
DOI: 10.1002/hyp.13656
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting dominant peak‐flow runoff‐generation mechanisms among five neighbouring granitic headwater catchments

Abstract: We examined how and why dominant peak-flow runoff-generation mechanisms differ among neighbouring headwater catchments. We monitored runoff and groundwater levels and performed terrain analyses in a granitic second-order catchment and its four neighbouring subcatchments in the Kiryu Experimental Watershed in Japan. Our analysis of lag times from peak rainfall to peak runoff suggests differences in the dominant peakflow runoff-generation mechanisms among the five catchments. For two of the three zero-order catc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Since the total area of the individual study sites in the current study (Table 1) was smaller than this, the spatial variation in precipitation would be too small to cause the increase in baseflow-specific discharge with area by an order of one for the volcanic sites (Figure 3). As for the participation of storm flow, Iwasaki et al (2020) also reported that a subcatchment with the smallest baseflow-specific discharge had a relatively small direct runoff ratio by comparing five subcatchments in a granitic headwater catchment. Takahashi et al (1982) found that direct runoff ratio was not correlated to catchment area by examining 58 catchments with various bedrock geology between 1 and 1,000 km 2 .…”
Section: Differences In the Specific Discharge Scaling Relationships Between The Volcanic And Sedimentary Sitesmentioning
confidence: 99%
“…Since the total area of the individual study sites in the current study (Table 1) was smaller than this, the spatial variation in precipitation would be too small to cause the increase in baseflow-specific discharge with area by an order of one for the volcanic sites (Figure 3). As for the participation of storm flow, Iwasaki et al (2020) also reported that a subcatchment with the smallest baseflow-specific discharge had a relatively small direct runoff ratio by comparing five subcatchments in a granitic headwater catchment. Takahashi et al (1982) found that direct runoff ratio was not correlated to catchment area by examining 58 catchments with various bedrock geology between 1 and 1,000 km 2 .…”
Section: Differences In the Specific Discharge Scaling Relationships Between The Volcanic And Sedimentary Sitesmentioning
confidence: 99%
“…Similar to the pattern found in training losses, this phenomenon became more significant when the lead time of the forecasting increased, although it was not evident in the Tþ1 forecasting in the WRB. This can be partially explained by the time lag effect of the hydrologic responses (Ross et al 2019;Iwasaki et al 2020). The time lag of the rainfall-runoff events makes the rainfall data meaningful to the target streamflow data.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the organization and distribution of landscape units can control the differences in runoff responses between nested catchments (Sidle et al 2000;McGlynn, McDonnell, Seibert, and Kendall 2004;Iwasaki et al, 2020). Iwasaki et al (2020) studied 5 catchments with similar geology, climate and vegetation, but different geomorphological layout, and concluded on the key role of the riparian area in buffering fast hillslope flow mechanisms.…”
Section: The Hm Sectionmentioning
confidence: 99%
“…The contrasted hydrological response during summer in the KOE catchment -exhibiting no change in dominant hydrological processes -could be caused by:  the larger riparian zone and the gentle slopes in the downstream part of the catchment, buffering the inflow of quick runoff (Iwasaki et al, 2015, Iwasaki et al, 2020;…”
Section: The Hm Sectionmentioning
confidence: 99%
See 1 more Smart Citation